2016
DOI: 10.1016/j.radonc.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Beyond mean pharyngeal constrictor dose for beam path toxicity in non-target swallowing muscles: Dose–volume correlates of chronic radiation-associated dysphagia (RAD) after oropharyngeal intensity modulated radiotherapy

Abstract: Purpose/Objective(s) We sought to identify swallowing muscle dose-response thresholds associated with chronic radiation-associated dysphagia (RAD) after IMRT for oropharyngeal cancer. Materials/Methods T1-4 N0-3 M0 oropharyngeal cancer patients who received definitive IMRT and systemic therapy were examined. Chronic RAD was coded as any of the following ≥ 12 months post-IMRT: videofluoroscopy/endoscopy detected aspiration or stricture, gastrostomy tube and/or aspiration pneumonia. DICOM-RT plan data were aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 81 publications
2
43
1
Order By: Relevance
“…Pharyngeal constrictors and the larynx were first identified by multiple investigators as primary dysphagia-aspiration-related organs (DARS) [95]. Beyond the classic DARS, emerging work suggests relevance of dose/volume distributions to submental musculature (i.e., geniohyoid, mylohyoid) that are critical to elevate the hyolaryngeal complex and assist with cervical esophageal opening [96,97]. Reporting normal tissue complications probabilities as a function of DARS, Eisbruch et al gave solid ground for efforts to reduce dysphagia in the IMRT era [95,98,99].…”
Section: Dysphagiamentioning
confidence: 99%
“…Pharyngeal constrictors and the larynx were first identified by multiple investigators as primary dysphagia-aspiration-related organs (DARS) [95]. Beyond the classic DARS, emerging work suggests relevance of dose/volume distributions to submental musculature (i.e., geniohyoid, mylohyoid) that are critical to elevate the hyolaryngeal complex and assist with cervical esophageal opening [96,97]. Reporting normal tissue complications probabilities as a function of DARS, Eisbruch et al gave solid ground for efforts to reduce dysphagia in the IMRT era [95,98,99].…”
Section: Dysphagiamentioning
confidence: 99%
“…The second set of limitations are inherent to models themselves, either due to patient case mix or statistical methods employed. For example a recent publication showed that late dysphagia was related to a different set of muscle dose constraints than in the models used here [9,10], which could be related to the inclusion of only oropharyngeal cancer and the use of a recursive partitioning approach in this latter publication [21]. Indeed the majority of NTCP models investigated in the present study are based on logistic regression, which makes assumptions with regards to dose-toxicity relationship that are valid only for a subset of toxicities, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy induces treatment related toxicities correlated to the RT dose delivered to normal tissues ( 12 , 13 ). Moreover, concomitant systemic treatment significantly increases the acute and late toxicity ( 6 , 14 ).…”
Section: Changes In Primary (Chemo)radiotherapymentioning
confidence: 99%